2007
DOI: 10.1117/1.2715202
|View full text |Cite
|
Sign up to set email alerts
|

Application of fluorescence recovery after photobleaching to study prestin lateral mobility in the human embryonic kidney cell

Abstract: The transmembrane protein prestin is crucial to outer hair cell (OHC) electromotility and contributes to the sensitivity and frequency selectivity of mammalian hearing. The molecular mechanisms of electromotility remain unclear, but prestin is purported to function as both a voltage sensor and a molecular motor. Understanding the role of prestin requires characterizing its organization and behavior in the plasma membrane. Fluorescence recovery after photobleaching (FRAP) provides a powerful means to quantitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 50 publications
2
7
0
Order By: Relevance
“…In expression systems, such as in HEK cells, the lateral diffusion of GFP-labeled prestin appears, on the basis of FRAP experiments, to be considerably lower than expected for freely diffusing proteins (254). This study suggests that there may be intermolecular interactions between prestin and a lipid membrane and/or the underlying cytoskeleton, even in these cells.…”
Section: A Density Of the Motor Proteinmentioning
confidence: 85%
“…In expression systems, such as in HEK cells, the lateral diffusion of GFP-labeled prestin appears, on the basis of FRAP experiments, to be considerably lower than expected for freely diffusing proteins (254). This study suggests that there may be intermolecular interactions between prestin and a lipid membrane and/or the underlying cytoskeleton, even in these cells.…”
Section: A Density Of the Motor Proteinmentioning
confidence: 85%
“…This discrepancy probably relates to the diffusibility of prestin in the plasma membrane. The prestin molecules are considered to be diffusible in the lateral plasma membrane of OHCs [34][35][36][37][38][39]. In addition, in between the intramembrane molecules, including prestin, there are some spaces [13][14][15][16][17][18].…”
Section: Membrane Topology Of Prestin In the Plasma Membranes Of Cho mentioning
confidence: 99%
“…In addition, depletion of membrane cholesterol enhances the mechanical response of OHCs to electrical stimuli (19). Moreover, confocal fluorescence images of prestin-transfected cells show punctate foci in the membrane (16,17,20,21). Puncta reversibly disappear upon cholesterol depletion and colocalize with known lipid raft markers (16,17).…”
Section: Introductionmentioning
confidence: 97%
“…Early indications that prestin is mobile came from indirect electrophysiological measurements (24,25). Later, direct measurements of prestin diffusion employing fluorescence recovery after photobleaching (FRAP) revealed that immobile fractions remained after dual bleaches, suggesting that prestin is transiently confined (20). However, because FRAP is an ensemble measurement, a detailed analysis of the size and character of the putative confinements was not possible, and other, more-complex modes of diffusion could not be ruled out (20).…”
Section: Introductionmentioning
confidence: 99%